Deficiency of host CD96 and PD-1 or TIGIT enhances tumor immunity without significantly compromising immune homeostasis. (3rd July 2018) - Harjunpää, Heidi; Blake, Stephen J.; Ahern, Elizabeth; Allen, Stacey; Liu, Jing; Yan, Juming; Lutzky, Viviana; Takeda, Kazuyoshi; Aguilera, Amy Roman; Guillerey, Camille; Mittal, Deepak; Li, Xian Yang; et al.
ABSTRACT: Multiple non-redundant immunosuppressive pathways co-exist in the tumor microenvironment and their co-targeting can increase clinical responses. Indeed, concurrent blockade of CTLA-4 and PD-1 in patients with advanced melanoma increased clinical responses over monotherapy alone although the frequency and severity of immune related adverse events (irAEs) also increased. Nevertheless, a substantial number of patients still display an innate resistance phenotype and are unresponsive to current approved immunotherapies even when utilized in combination. In this study, we generated Pdcd1 − / − CD96 − / − and Tigit − / − CD96 − /− mice to investigate how loss of CD96 in combination with PD-1 or TIGIT impacts on immune homeostasis and hence the potential of inducing immune related toxicities following co-targeting of these pairs of receptors. The ability of Pdcd1 − / − CD96 − / − and Tigit − / − CD96 − /− mice to suppress primary tumor growth was also assessed using the MC38 colon carcinoma and SM1WT1 BRAF-mutated melanoma tumor models. Both Pdcd1 − / − CD96 − / − or Tigit − / − CD96 − /− mice displayed no overt perturbations in immune homeostasis over what was previously reported with Pdcd1 − / − or Tigit − / − mice even when aged for 22 months. Interestingly, increased suppression of subcutaneous tumor growth and complete responses was seen in Pdcd1 − / − CD96 − / − mice compared to Pdcd1 − / − or CD96 − / − mice depending upon the tumor model. In contrast, in these models, growth suppression in Tigit − / − CD96 − / − were similar to Tigit − / − or CD96 − / − . This enhanced anti-tumor efficacy of Pdcd1 − / − CD96 − / − appeared to be due to favorable changes in the ratio of CD8 + T cells to T regulatory cells or CD11b + GR-1 hi myeloid cells in the tumor microenvironment. Co-targeting CD96 and PD-1 may increase anti-tumor immunity over targeting PD-1 alone and potentially not induce serious immune-related toxicities and thus appears a promising strategy for clinical development.